Long-term Anamnesis of Chronic Thromboembolic Pulmonary Disease. Does it Predict the results of Pulmonary Thromboendarterectomy? (London Journal of Medical and Health Research, 2025)
Abstract.Introduction: Pulmonary thromboendarterectomy (PEA) is the main method of treatment for patients with chronic thromboembolic pulmonary hypertension (CTEPH). The residual pulmonary hypertension (PH) after CTEPH surgical treatment is a risk factor with increasing of hospital mortality.Objective: To analyze and evaluate the results of PEA in patients with different persistent time of medical history as a possible prognostic factor of residual PH and outcome.Methods: Retrospective and prospective analysis of the PEA results in 87 patients operated on from April 2012 to February 2022 was conducted. The patients were divided into 3 groups. The 1st group – 45 patients with a medical history from 3 months to 1 year, the 2nd – 20 patients from 1 year to 3 years and the 3rd -22 patients with long-term history more than3 years.Results: The average age of the patients was 48.7 ±13.5 years, including56.7% males and43.3% females. Due to New York Heart Association (NYHA),7(8.0%) patients preoperatively belonged to class II,60(69.0%) to class III and20(23.0%) to class IV. Postoperatively the mean pulmonary artery pressure (mPAP mmHg) and pulmonary vascular resistance (PVR dyn·s·cm⁻⁵) significantly decreased in all groups (mPAP:1st group from45±13 to23±6,2nd – from49±14 to25±6 and3rd – from58±12 to31±7; PVR:1st group from797±262 to290±135,2nd – from925±383 to376±159 and3rd – from1248±332 to505±189). Hospital mortality after PEA was0 in patients with medical history less than1 year,5% from1 to3 years and31% in patients with long-term anamnesis.Conclusions. PEA is an effective surgery with mPAP and PVR decreasing in the early postoperative period. However, long-term medical history and PVR >1000 dyn·s·cm⁻⁵ are very important risk factors with increasing of hospital mortality.
Keywords: Quality improvement; brazil; organ transplantation; management program; PAT-MA; health systems; Maranh; pulmonary hypertension.; Chronic thromboembolic pulmonary hypertension; Thrombendarterectomy; Pulmonary vascular resistance; Long-term medical history.